The Effects of Alcohol Outlets and Sales on Alcohol-Related Injuries Presenting at Emergency Departments in Perth, Australia, from 2002 to 2010 - Hobday, Michelle Bridget (Curtin University, 2014)
The study examined the effects of licensed outlets and alcohol sales on levels of alcohol-related injuries presenting to Emergency Departments in Perth, Western Australia . This retrospective population-based longitudinal study used injury and alcohol availability data. Negative binomial regression modelling with random effects demonstrated that sales per off-premise outlet and counts of on-premise outlets per postcode were significantly associated with alcohol-related injury. These findings also supported restrictions on numbers of outlets, price discounting, and trading hours.